Contemplation: Its Cultivation and Culmination Through the Buddhist Glasses - Chattopadhyay, Madhumita (Frontiers in Psychology, 2022)
Buddhist account of consciousness provides a new way of looking into contemplation, where absorption into meditation does not only bring in changes in the neural level but in the very personality of the individual, turning him into a good human being. The Buddhists recommend the practice of vipassanā, literally meaning insight but actually standing for the realization of the supreme enlightenment breaking off all the internal fetters through practice of seven different types of purity, like purity of morals, mind, views, insight etc. In early and later Buddhist literature, it has been categorically emphasized that one should not practice the solitary mindfulness but should practice to enrich the higher qualities of the mind like compassion, friendliness etc. The point is that the contemplated individual, the Bodhisattva should possess the perfection of wisdom (prajñā-pāramitā) and be equipped with the skill of upāyas. Practice of these upāyas, however, will not create any new bondage for the contemplative mind. When the individual is able to attain this broad outlook, he will be said to achieve the highest contemplation – this is the ultimate objective of Buddhist meditation. Meditation is needed for this change of outlook – transition from ‘I’ to ‘we’. This is the only way to bring in peace of mind, peace to the whole world.